UJI ORGANOLEPTIK PUPUK KOMPOS DARI KOTORAN SAPI DENGAN PENAMBAHAN DAUN LAMTORO DAN SEKAM - anam, Muchammad khoirul; Esti, Risma Novela; widyasworo, Agustina (AVES: Jurnal Ilmu Peternakan, 2023)
The purpose of this research is to find out about making compost from cow dung with the addition of lamtoro leaves and husks. The research method used is using a questionnaire involving 40 people as panelists who will see the quality of the compost based on texture, smell and color. compost. With 3 repetitions for each treatment. Based on the research results, the best treatment in this study was P3 with the addition of 50% lamtoro leaves and 50% husks. Based on the results of this study, it is recommended for further research that the husks used are burned briefly first so that the husks become smooth and the composting process can be optimal with fine husk conditions.